Identification of Polo-like kinases as potential novel drug targets for influenza A virus - Marie O. Pohl (Nature Portfolio, 2017)
Abstract In recent years genome-wide RNAi screens have revealed hundreds of cellular factors required for influenza virus infections in human cells. The long-term goal is to establish some of them as drug targets for the development of the next generation of antivirals against influenza. We found that several members of the polo-like kinases (PLK), a family of serine/threonine kinases with well-known roles in cell cycle regulation, were identified as hits in four different RNAi screens and we therefore studied their potential as drug target for influenza. We show that knockdown of PLK1, PLK3, and PLK4, as well as inhibition of PLK kinase activity by four different compounds, leads to reduced influenza virus replication, and we map the requirement of PLK activity to early stages of the viral replication cycle. We also tested the impact of the PLK inhibitor BI2536 on influenza virus replication in a human lung tissue culture model and observed strong inhibition of virus replication with no measurable toxicity. This study establishes the PLKs as potential drug targets for influenza and contributes to a more detailed understanding of the intricate interactions between influenza viruses and their host cells.